Pengembangan Media Poster Kultur Jaringan di FKIP Biologi UIR - Mellisa Mellisa; Sri Amnah; Destry Hardiyanty (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2022)
This research on the development of tissue culture poster media using the ADDIE model has three stages, namely, analysis, design, and development. Determination of the sample of this study using the purposive sampling technique. The data collection technique used a validation sheet by material experts and media experts and saw student responses to the poster developed by conducting a limited feasibility test. The data analysis technique used descriptive analysis. The results of this study are in the form of printed products, namely tissue culture posters. The results of validation by material experts indicate that the poster developed is very feasible to use with an average percentage of 95.83%. The results of the validation by media experts showed that the poster developed was very feasible to use with an average percentage of 97.36. The results of student responses from two classes get an average percentage of 95.31% (very feasible). Based on the validation results from the experts, the product in the form of a tissue culture poster is very feasible to be used in the learning process. Penelitian pengembangan media poster kultur jaringan ini menggunakan model ADDIE memiliki tiga tahap yaitu, analisis, perancangan, dan pengembangan. Penentuan sampel penelitian ini menggunakan teknik purposive sampling. Teknik pengumpulan data menggunakan lembar validasi oleh ahli materi dan ahli media serta melihat respon mahasiswa terhadap poster yang dikembangkan dengan melakukan uji coba kelayakan terbatas. Teknik analisis data menggunakan analisis deskriptif. Hasil penelitian ini adalah berupa produk cetak yaitu poster kultur jaringan. Hasil validasi oleh ahli materi menunjukkan bahwa poster yang dikembangkan sangat layak digunakan ratarata persentase 95,83%. Hasil  validasi oleh ahli media menunjukkan bahwa poster yang dikembangkan sangat layak digunakan dengan rata-rata persentase 97,36. Hasil respon mahasiswa dari dua kelas mendapatkan rata-rata persentase 95,31% (sangat layak).  Berdasarkan hasil validasi dari para ahli diperoleh produk berupa poster kultur jaringan yang sangat layak untuk digunakan dalam proses pembelajaran.Kata kunci: kultur jaringan, nibung, penelitian pengembangan, poster DOI: http://dx.doi.org/10.23960/jbt.v10i1.24224